Knowledge of nursing students towards HIV/AIDS in Nepal - Parajulee, Sita; Selvaraj, Valarmathi (Journal of College of Medical Sciences-Nepal, 2013)
Aims First case of Acquired Immuno Deficiency Syndrome (AIDS) in Nepal was reported in the year 1988. Nurses are an integral part of the healthcare system and should be knowledgeable in providing care to AIDS patients. This study assessed the knowledge of nursing students towards HIV/AIDS, and the association (if any) between the knowledge scores of the nursing students with their selected demographic variables. Materials and methods A cross sectional study was conducted evaluating the nursing student knowledge using a self designed questionnaire. The correct answers were given a score of ‘1’ and wrong answers were given a score of ‘0’ (total possible maximum score ‘18’). Results Among the total 165 nursing students, 121 of them filled the questionnaire (response rate of 73.33%) and all of them were females. The mean ± SD age of the respondents was 18.3 ±1.75 years. The median (IQR) of the overall total scores was 13.0 (11.5-15.0). There was an association between the knowledge scores of the respondents with ‘age’ (p=000), ‘course of the study’ (p=0.001). However, there was no statistically significant association between the knowledge scores with the ‘year of study’ of the respondents (p=0.109), ‘mode of finance’ (0.611) and ‘native’ of the students (0.173). Conclusion The study suggested that nursing students have a poor overall knowledge on AIDS and especially areas such as post exposure prophylaxis.The findings also suggested the need for providing adequate knowledge to the students during their regular class room teaching and clinical postings. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 27-33 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8697